Penggunaan Film Anime Untuk Meningkatkan Keterampilan Mendengar Dan Berbicara Bahasa Arab Di Madrasah Aliyah Darul Lughah Wa Da’wah Bangil, Pasuruan - Baharun, Segaf; Fauzi Hamzah, Achmad; Abidin, Zainal (Sekolah Tinggi Ilmu Tarbiyah Tihamah, 2024)
Learning Arabic is often considered difficult because of the challenges students face. The use of anime films as a learning medium has proven effective in improving listening and speaking skills. Arabic anime enriches vocabulary, improves pronunciation, and helps students understand intonation and accent in everyday conversation. The combination of visuals and audio makes learning more interesting and motivates students. Imitating anime dialogue can improve your speaking skills in a relaxed atmosphere. Facilities such as projectors and internet access are important to maximize its effectiveness. The anime also introduces authentic conversational situations and Arabic cultural context. However, there are obstacles such as limited access to quality films and technical challenges regarding audio quality. Excessive reliance on anime can also reduce the variety of learning methods, so it needs to be balanced with other methods.